Multi-scenario Simulation and Water Resource Effects of Integrated Utilization of Saline-alkali Land in Western Jilin Province - LI Wenbo; JIANG Bowen; WANG Jingying (Shuitu Baochi Xuebao, 2024)
[Objective] The integrated utilization of saline-alkali land remains a quintessential stratagem to enhance grain yield whilst embracing the principle of Greater Food. The current simplistic reclamation approaches and the intensive water demands, however, call for a thorough investigation of diversified management strategies and interventions that take into account the impact on water resources. [Methods] The study selected the western part of Jilin province as the study area and adopted the FLUS model to forecast the utilization patterns of saline-alkali land resources until 2030 under four scenarios: Natural progression, grain security, integration of grain and forage production, and ecological protection. The InVEST model was then applied to evaluate the variations in water yield across these scenarios. [Results] (1) From 2000 to 2020, 1 540.18 km2 of saline-alkali land in the study area was put to use, predominantly restored to grassland or reclaimed as cultivated land, with a substantial risk of secondary salinization in drylands. (2) Under all scenarios, the reclamation of saline-alkali land for agriculture prevailed. In the grain security scenario, the paddy fields and drylands accounted for 67.48% and 4.23%, respectively. When compared with the natural progression scenario, the grassland area was set to expand by 139.18 km2 in the integration of grain and forage production scenario, and ecological land would increase substantially under the ecological protection scenario. (3) By 2030, water yield is projected to decrease in all four scenarios relative to the baseline period, with the ecological protection scenario facing the steepest reduction at 3.71×108 m3. Conversely, the integration of grain and forage scenario offered a well-balanced solution, ensuring the output of crops and forage while easing the water pressures initiated by the management of saline-alkali land. [Conclusion] Utilization of saline-alkali land in the Songnen Plain requires a balanced and strategic approach that supports both grain and forage production. Efforts should be made on maintaining the equilibrium between the supply of agricultural and fodder resources whilst ensuring food and ecological security. The overarching goal is to regulate the ecological restoration of our territorial space and utilization of degraded lands following the concept of Greater Food.